2018
DOI: 10.1093/cid/ciy393
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Chlorhexidine Dressing on Silver-coated External Ventricular Drain–associated Colonization and Infection: A Prospective Single-blinded Randomized Controlled Clinical Trial

Abstract: NCT02078830.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The mechanisms behind the transition of hydrocephalus from an acute to a chronic condition have yet to be fully understood. Inflammation induced by EVDAI can lead to CSF circulation disturbances through ependymal cell dysfunction, CSF barrier cell inflammation with increased CSF secretion, and infectious debris blocking CSF outflow [8][9][10]. Interestingly, the present study demonstrated a higher ratio of catheter colonization to EVDAI in the early group than in the late group (7/1 out of 20 patients vs. 7/7 out of 19 patients; Table 2).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The mechanisms behind the transition of hydrocephalus from an acute to a chronic condition have yet to be fully understood. Inflammation induced by EVDAI can lead to CSF circulation disturbances through ependymal cell dysfunction, CSF barrier cell inflammation with increased CSF secretion, and infectious debris blocking CSF outflow [8][9][10]. Interestingly, the present study demonstrated a higher ratio of catheter colonization to EVDAI in the early group than in the late group (7/1 out of 20 patients vs. 7/7 out of 19 patients; Table 2).…”
Section: Discussionmentioning
confidence: 54%
“…From a pathophysiological perspective, longer EVD duration promotes progressive catheter colonization from growing skin flora contaminants over time that might induce inflammatory processes. Pathogens at the skin site and CSF leakage were found to be independent predictors of EVDAI [9,38]. As previously discussed, a predisposition for bacterial infection induced by immunodepression might accentuate this risk specifically in the subset of aSAH patients [4][5][6]37].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations